Investigating the Efficacy of the Papago AI Application in Enhancing Vocabulary Proficiency Among Secondary School Students - Kholid, M. Fikri Nugraha; Adillia, Anisa; Suryawati, Sri Suci (LinguaEducare: Journal of English and Linguistic Studies, 2025)
This quasi-experimental study investigated the efficacy of the AI-powered Papago application in enhancing vocabulary acquisition among tenth-grade students at SMAN 7 Bandar Lampung. The research aimed to address common student difficulties in vocabulary retention and application by leveraging AI's potential for personalized, contextually accurate, and interactive learning. Focusing on five key vocabulary categories—nouns, adjectives, adverbs, verbs, and conjunctions, particularly within the context of descriptive texts—the study employed a quantitative research design to assess Papago's impact. Data were collected via pre-tests and post-tests, supplemented by qualitative feedback from students and teachers regarding the application's usability. Statistical analysis using SPSS 27 revealed a significant difference (p=0.004<0.05) in vocabulary mastery among students who utilized Papago. This outcome supports the alternative hypothesis, indicating that the intervention effectively improved students' vocabulary mastery. The findings suggest that AI applications such as Papago hold considerable promise in surmounting prevalent vocabulary-learning challenges and fostering greater student engagement.